Assessment and management of environmental risks from industries at Trans–Thane Creek, Bombay. (4th August 2014) - Ghosh, P.K.
This paper gives an overview of the risk assessment study carried out as part of the Inter–Agency Project on Assessment and Management of risks from industries in the Trans–Thane Creek area near Bombay. The scope of the study includes identification of hazardous chemicals in the industrial area, reviewing the possible sources of release of the chemicals, evaluating probable reasons for such releases, determining the vulnerable zones, and evaluating risk reduction measures. The study involving hazard identification and consequence analysis was carried out by a working group of which the author was the convener.